The Predictive Value of Mca/Ua Pulsatility Index Ratio in Adverse Perinatal Outcomes among Women with Preeclampsia and Gestational Hypertension - Dr. T. Shireesha, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Preeclampsia and gestational hypertension are significant causes of maternal and fetal morbidity and mortality worldwide. The middle cerebral artery to umbilical artery (MCA/UA) pulsatility index ratio has emerged as a potential predictor of adverse perinatal outcomes in these conditions. Methods: A prospective observational case-control study was conducted on 200 pregnant women diagnosed with preeclampsia or gestational hypertension after 30 weeks of gestation. Doppler ultrasound was used to measure the MCA/UA pulsatility index ratio. Women with a ratio ≤1 were categorized as cases, and those with a ratio >1 as controls. Adverse perinatal outcomes were recorded and analyzed. Results: Of the 200 women, 52 (26%) had an MCA/UA ratio ≤1. The cases showed a significantly higher incidence of severe oligohydramnios (26.9% vs. 6.7%, p<0.0001), emergency cesarean sections (71.15% vs. 37.16%, p=0.00027), low birth weight (<2.5 kg) infants (59.61% vs. 25.67%, p<0.00001), and NICU admissions (68.62% vs. 30.55%, p<0.00001). The MCA/UA ratio demonstrated a sensitivity of 39.04% and specificity of 88.40% in predicting adverse perinatal outcomes. Conclusion: An abnormal MCA/UA pulsatility index ratio (≤1) is significantly associated with adverse perinatal outcomes in women with preeclampsia and gestational hypertension. Routine use of this Doppler parameter can aid in early identification and management of at-risk pregnancies.